Peningkatan Pengetahuan Lansia Melalui Edukasi Tuberkulosis (TB) Di Posyandu Lansia Puskesmas Belimbing, Padang - Shelvy Haria Roza; Sarah Sausan Khalisa; Shirli Rizki; Suci Rahmahesi; Velia Windy Abel (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
This program aims to increase the elderly's knowledge about TB prevention and control through the “Market TB” (Let's Recognize and Treat TB) outreach activity. The activity was carried out at the Belimbing Community Health Centre’s elderly health post. The method used was a lecture using posters, accompanied by pre-tests and post-tests to measure the increase in knowledge. Interactive discussions were held to reinforce participants' understanding. Educational posters were also displayed in strategic locations to expand the reach of information. The results showed an increase in the average post-test score (8.11) from the pre-test score (5.05). The outreach activities were carried out successfully, as evidenced by the active participation of the target audience and a 3.06-point increase in knowledge scores after the intervention. Posters and participatory outreach methods proved effective in conveying health information to the elderly. The Belimbing Community Health Centre is expected to continue providing regular education on tuberculosis to the elderly using visual approaches and simple language that is easy to understand. In addition, youth posts can be utilized as an educational medium by providing health information that is easily accessible to the community. Posyandu cadres also need to be actively involved as an extension of health workers in disseminating community-based health information, so that education can reach a wider audience and be sustainable.